Hydromechanical analysis of the second hydraulic stimulation in well PX-1 at the Pohang fractured geothermal reservoir, South Korea. (January 2021) - Farkas, Márton Pál; Hofmann, Hannes; Zimmermann, Günter; Zang, Arno; Bethmann, Falko; Meier, Peter; Cottrell, Mark; Josephson, Neal
Highlights: Coupled hydro-mechanical simulation and characterization of the cyclic soft stimulation in August 2017 at the Pohang EGS reservoir (second stimulation in well PX-1) is performed. Pressure history match was achieved by splitting the simulated treatment into phases. The permeability is increased through opening of existing fault. The modeled extent of direct overpressure of 0.01 MPa at the end of the stimulation is approx. 180 m from the injection point. Abstract: In this study, we investigate numerically the hydro-mechanical behavior of fractured crystalline rock due to one of the five hydraulic stimulations at the Pohang Enhanced Geothermal site in South Korea. We use the commercial code FracMan (Golder Associates) that enables studying hydro-mechanical coupled processes in fractured media in three dimensions combining the finite element method with a discrete fracture network. The software is used to simulate fluid pressure perturbation at fractures during hydraulic stimulation. Our numerical simulation shows that pressure history matching can be obtained by partitioning the treatment into separate phases. This results in adjusted stress-aperture relationships. The evolution of aperture adjustment implies that the stimulation mechanism could be a combination of hydraulic fracturing and shearing. The simulated extent of the 0.01 MPa overpressure contour at the end of the treatment equals to ∼180 m around the injection point.